Room Borrowing Information System Website Based using PHP and MySQL with Waterfall Model - Doni Oktaviana; Mustofa Abi Hamid (Universitas Ahmad Dahlan, 2021)
Research by developing an information system is a research that aims to produce and develop an information service system design in the form of website-based rooms lending using PHP as a programming language and MySQL as a database that will be used at the Faculty of Teacher Training and Education, Sultan Ageng Tirtayasa University in-room management as room loan, room loan schedule, room loan data, and room information. This study uses the waterfall development model, with 5 (five) stages of development including the stages of communication, planning, modelling, construction and deployment. This research used Alpha and Beta testing to 3 (three) media experts and 31 (thirty-one) users including 1 (one) admin and 30 (thirty) students. Data collection techniques using interview techniques, observation and dissemination of research instruments. With data analysis in the form of a feasibility test using a Likert scale instrument of 4 (four) assessment scores to media experts and respondents. The final product produced is a website for rooms loaning information system, by average score by media experts (Alpha Testing) of 71.6 with the